2020
DOI: 10.1002/adma.202002032
|View full text |Cite
|
Sign up to set email alerts
|

Proximity‐Coupling‐Induced Significant Enhancement of Coercive Field and Curie Temperature in 2D van der Waals Heterostructures

Abstract: Magnetism in 2D has long been the focus of condensed matter physics due to its important applications in spintronic devices. A particularly promising aspect of 2D magnetism is the ability to fabricate 2D heterostructures with engineered optical, electrical, and quantum properties. Recently, the discovery of intrinsic ferromagnetisms in atomic thick materials has provided a new platform for investigations of fundamental magnetic physics. In contrast to 2D CrI3 and Cr2Ge2Te6 insulators, itinerant ferromagnetic F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
139
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 40 publications
0
139
0
4
Order By: Relevance
“…successfully observed the improved ferromagnetic property of 2D FePS 3 /Fe 3 GeTe 2 heterostructure through MOKE measurement (Figure 6c). [ 111 ] Benefitting from the proximity coupling effect, the heterostructure shows higher Curie temperature and much stronger coercive field than Fe 3 GeTe 2 flakes alone. [ 111 ] Recent work has demonstrated that the antiferromagnetic phase transition in 2D FePS 3 flakes can be probed by nanomechanical resonators and revealed that specific heat plays a mediated role between mechanical motion and antiferromagnetic order (Figure 6d,e).…”
Section: Novel Properties Of 2d Lpcsmentioning
confidence: 99%
See 2 more Smart Citations
“…successfully observed the improved ferromagnetic property of 2D FePS 3 /Fe 3 GeTe 2 heterostructure through MOKE measurement (Figure 6c). [ 111 ] Benefitting from the proximity coupling effect, the heterostructure shows higher Curie temperature and much stronger coercive field than Fe 3 GeTe 2 flakes alone. [ 111 ] Recent work has demonstrated that the antiferromagnetic phase transition in 2D FePS 3 flakes can be probed by nanomechanical resonators and revealed that specific heat plays a mediated role between mechanical motion and antiferromagnetic order (Figure 6d,e).…”
Section: Novel Properties Of 2d Lpcsmentioning
confidence: 99%
“…[ 111 ] Benefitting from the proximity coupling effect, the heterostructure shows higher Curie temperature and much stronger coercive field than Fe 3 GeTe 2 flakes alone. [ 111 ] Recent work has demonstrated that the antiferromagnetic phase transition in 2D FePS 3 flakes can be probed by nanomechanical resonators and revealed that specific heat plays a mediated role between mechanical motion and antiferromagnetic order (Figure 6d,e). [ 22 ] Moreover, the strong dependence between the Neel temperature and electrostatically induced strain in 2D FePS 3 flakes has also been confirmed.…”
Section: Novel Properties Of 2d Lpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assembling the vdW heterostructure with other materials may also be helpful in enhancing the T C of vdW magnets. [163,171,172] In addition, doping, such as, Ga implantion and Co doping were recently demonstrated to be effective to increase the T C . [173][174][175] Finally, wafer-scale scalability of vdW materials is still an important issue.…”
Section: Discussionmentioning
confidence: 99%
“…2D MPTs exhibit larger bandgaps than current 2D transition metal chalcogenides (TMDs), which satisfies the application demands in the broad wavelength response [9]. Accordingly, 2D MPTs are supposed to provide appealing prospects in photodetection, catalysis, and spintronic devices, and expected to be a powerful candidate of next-generation electronics [10][11][12].…”
Section: Introductionmentioning
confidence: 99%